The Communicative Linguistic Landscape. Production formats and designed environments, by Lionel Wee, New York: Routledge, 2021, 186 pp., ISBN: 9780367701031 - Zhao, Yufan; Wang, Jiayu (Círculo de Lingüística Aplicada a la Comunicación, 2025)